PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN BONTANG BARAT - Ayu Dita Sari; Mega Fatmawati; Martopan Abdullah (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Research has been carried out on the effect of motivation and work discipline on the performance of West Bontang District employees. Sampling of the questionnaire was carried out on 30 employees in the West Bontang sub-district. Testing the results is done by testing multiple regression analysis, F test, t test and R2 test. In multiple linear regression testing, Y = -10,791+ 0, 364 X1 + 0, 785 X2. F count shows the value = 28,532. This shows that the value of Fcount > Ftable, which is 28.532 > 3.1618 and the significance level is 0.000 <0.05. Thus, Motivation (X1) and Discipline (X2) have a significant positive effect on employee performance (Y) as the dependent variable. The t-count variable X1 is greater than the t-table value (2.198>1.703) with a significant level below 0.05, which is 0.000 and the t-count variable is greater than the t-table value (6.548>1.703) with a significant level below 0.05, i.e. 0.000 . Based on the method of decision making in the partial test in regression analysis, it can be concluded that: the work discipline variable is more dominant in influencing employee performance. Motivation and work discipline can simultaneously affect employee performance because the significant value is below 0.05, namely 0.000 (sig < 0.05). These results indicate that motivation and work discipline are factors that play an important role in determining the level of improvement in employee performance. The results of the analysis also show that the variable t value = 6.548> t arithmetic variable = 2.198, it can be concluded that the work discipline variable has a more dominant effect on employee performance in the West Bontang sub-district. Keywords: Motivation, Work Environment and Employee Performance